Guided note taking based on students worksheet effect towards students learning outcome. (February 2020) - Febriana, E; Hasanuddin,; Huda, I; Supriatno,; Sarong, M A
Abstract: This research aims to discover the effect of students worksheet based on guided note taking towards the learning outcome of students both individually and as a group. The method implemented in this research is Quasi-experimental research with the Nonequivalent Control Group Design of 138 population and 82 students as samples. Instruments used in this research are multiple-choice questions to measure the learning outcomes, syllabus, learning implementation plan, and learners' worksheets. The data collection process was conducted by looking for the post-test and pre-test values as well as t-test to compare it to pre-test and post-test scores. Data analysis was conducted using an Independent Sample T-test testing at a significant level of 0.05. The result of Independent Sample T-test testing at the outcome of control class indicates that the outcome (Mean=77, 48, Standv=4.830) is different from the value in experiment class (Mean=84.93, Standv=3.672), tcount = 7.89 > ttable 1.66 at the Sig. (2-tailed) level of 005. It can be concluded that students who use the guided-note-taking based learners' worksheet as a group show a better learning outcome compared to the students who use guided-note-taking based learner worksheets individually at Ingin Jaya High School Aceh Besar.